THE POTENTIAL OF DIALECT PHONETIC MISTAKES IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Martins Medina, Suellen; Budnik, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article examines the problem of presenting phonetic material in texts when teaching Russian as a foreign language (RFL) to Brazilian students. Based on the methodological principles of teaching Russian phonetics, the authors discuss the importance of taking into account students' phonetic needs in selecting text in the educational process. The structure of educational materials and educational texts are analysed as an example of this approach. The authors offer to consider the national specifics of students to increase the efficiency of work on phonetics. To analyse the phonetic material present in texts and expose the specific difficulties Brazilian students experience when learning the Russian language, the authors experimented using a text from the textbook "Poekhali! 1 level". From different regions, fifty-four students were interviewed, and we presented different phonetic problems according to their dialectal characteristics. The most exciting and complex phonetic error is related to the pronunciation of the sounds [r]-[rʲ] and [X]-[Xʲ]; based on this type of error it is possible to determinate the provenience of the interviewed students.